Vanishing Lung Syndrome in a Dog: Giant Pneumatocele or Giant Pulmonary Bulla Mimicking Tension Pneumothorax—First Report - Jack-Yves Deschamps; Nour Abboud; Pierre Penaud; Françoise A. Roux (Veterinary Sciences)
A 6-month-old neutered male Belgian Malinois dog living in a kennel was presented to a veterinary emergency service for the management of severe respiratory distress that had developed within the past 24 h. Thoracic radiographs performed by a referring veterinarian showed abnormalities identified as a pneumothorax. Upon admission to the emergency service, the striking anomalies turned out to be a large intrathoracic air-filled cavity and countless smaller ones causing mechanical compression of the adjacent pulmonary parenchyma and mimicking tension pneumothorax. Emergency management included thoracocentesis followed by placement of a thoracostomy tube. The dog exhibited rapid clinical improvement and recovered completely within a few days, without requiring surgical intervention. Serial follow-up radiographs showed progressive and complete resolution of all lesions. Based on the complete resolution without resection, the main lesion—initially interpreted as a giant pulmonary bulla—was ultimately considered consistent with an acquired pneumatocele. To the authors’ knowledge, this is the first report in veterinary medicine of a vanishing lung syndrome presentation in a dog.